Polyarteritis nodosa. Diagnostic challenges in a patient with cutaneous vasculitis, psoriasis, psoriatic arthritis and pancytopenia: fatal progression after treatment with G-CSF. Issue 4 (26th April 2016) - Jobanputra, Paresh
Abstract: A 60-year-old man presented with cutaneous vasculitis, leucopenia and psoriasis. He was treated initially with ciclosporin A. On withdrawal of ciclosporin, due to inadequate improvement of cutaneous vasculitis, he developed psoriatic arthritis. Worsening neutropenia and pancytopenia, believed to be immune mediated, developed. He was treated with prednisolone, methotrexate and adalimumab but developed pneumocystis pneumonia. Leucocyte levels improved markedly with granulocyte colony-stimulating factor (G-CSF). However, whilst being treated with G-CSF his condition deteriorated. He developed gastrointestinal and neurological symptoms and progressive weight loss. Diagnosis was delayed, but eventually polyarteritis nodosa was diagnosed and he was treated with cyclophosphamide. The patient improved initially but died from small bowel perforation due to vasculitis. Evidence showing a temporal association of his deterioration with use of G-CSF is shown. The use of G-CSF in patients with autoimmune conditions including vasculitis should be undertaken with great caution.